I- Float / Low Cost and Multi-Purpose Emergency Float - Saiful Bahari, Mohd Yusoff; Mohamad Hafiza, Ab Razab (UNIMAS Publisher, Universiti Malaysia Sarawak, 2019)
Nowadays we hear many news of drowning cases especially during school holidays. People who go for water recreational pleasure at the beach, waterfall, pool and water sport do not usually carry around life jackets. Not everyone could afford to buy a life jacket. Life jackets are usually available only when riding water transports that are normally provided by the company. Most reasons found that life jackets are to be expensive to buy, too bulky to carry, uses too much space and others. When people go on holidays, they also consume plenty of water. Mineral or drinking bottles are often thrown away after they have finished drinking and some are not disposed properly which contributed to the pollution. Hence, i-Float is designed as an innovative floating device which can be used by anyone of all ages during water emergency. i-Float is able to keep user afloat continuously above water surface hence help users from drowning. i-Float has high commercial potential and is ready for low cost mass production. Therefore, i-Float or Low Cost and Multi-Purpose Emergency Float is created to overcome the issue. The application of waste material into life saving gadget that is lightweight and easy to assemble that makes this i-float useful and practical.